FACTORS AFFECTING DETACHMENT 88'S PERFORMANCE: INFORMATION TECHNOLOGY, RECRUITMENT AND TRAINING - Rochyadi Mangkuprdaja, Didi; Ali, Hapzi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Previous research or related research is very important in a study or scientific work. Previous research or related research reinforces theories and phenomena of relationships or influences between variables. This article examines the factors that affect the performance of the Special Section of Densus 88, namely information technology, recruitment and training, dissertation research in human resource management. The purpose of writing this article is to make hypotheses about the influence between variables to be used in future research. The results of this variable are: 1) Information Technology affects the Performance of Densus 88 2) Recruitment affects the Performance of Densus 88; and 3) Training affects the performance of Detachment 88.